2011
DOI: 10.1007/s00223-011-9516-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile of Steroid-induced Necrosis of Femoral Head of Rats

Abstract: The key to treating steroid-induced necrosis of femoral heads (SINFH) is early diagnosis. Dramatic improvements in diagnosis could be made if the pathogenesis of SINFH was more fully understood; however, the underlying mechanism of this disease is currently unknown. To explore the potential mechanism of SINFH, we performed gene array analysis on a rat model of the disease and compare the expression profile with that of normal rats. A quantitative RT-PCR and immunohistochemistry (IHC) assays were used to confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…In recent years, many attempts to elucidate the genetic contributors to SONFH have been undertaken. Tong et al [53] performed gene array analysis on a rat model of SONFH, confirmed the microarray results by using a quantitative RT-PCR and immunohistochemistry (IHC) assays. In their SONFH group, 190 individual genes showed differential expression relative to healthy controls, with 52 being upregulated and 138 being downregulated.…”
Section: Ratmentioning
confidence: 86%
“…In recent years, many attempts to elucidate the genetic contributors to SONFH have been undertaken. Tong et al [53] performed gene array analysis on a rat model of SONFH, confirmed the microarray results by using a quantitative RT-PCR and immunohistochemistry (IHC) assays. In their SONFH group, 190 individual genes showed differential expression relative to healthy controls, with 52 being upregulated and 138 being downregulated.…”
Section: Ratmentioning
confidence: 86%
“…High oxidative stress is thought to be associated with the development of various bone disorders, including osteoporosis [29,30], bone tumours [31], diabetic osteopenia [32], rheumatoid arthritis [33], and ankylosing spondylitis [34]. Recent evidence also indicated that ROS are involved in the pathogenesis of steroid-induced ONFH [20,21,35] and that approaches inhibiting oxidative stress exert potential therapeutic effects on ONFH [35][36][37]. To validate this, a ROS probe (DHE) was administrated on the rats prior to sacrifice, which is distributed via the circulation enabling the direct visualization of ROS in tissues as we previously described [18].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has demonstrated that ROS levels are increased during estrogen deficiency-induced osteoporosis in mice, and that antioxidant agents are effective in inhibiting osteoclast activity and thus preventing bone loss [18]. ROS have also been implicated in the pathogenesis of ONFH, causing damage to blood vessels and osteoblastic cell lineages [19][20][21]. However, the underlying mechanisms by which ROS levels change and cause the activation of the osteoclasts in the context of steroid-induced ONFH remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The 48 male adult rats were randomly distributed into three groups (12 in the control group, 24 in the Dex group, and 12 in the mir‐34a over‐expression lentivirus group). The rats in the Dex group were given two injections of lipopolysaccharide (LPS, 20 µg/kg, Sigma, MO) at an interval of 24 h, and then dexamethasone (40 mg/kg, Pfizer, NY) was injected into the gluteus muscle daily for 3 days, as described in a previous study . The animals in the lentivirus group received an extra intravenous injection of mir‐34a over‐expressing lentivirus at a dose of 1E + 8 TU (Genechem Co. Ltd, Shanghai, China) 1 day before LPS injection.…”
Section: Methodsmentioning
confidence: 99%